Filamentous green algae inhibit phytoplankton with enhanced effects when lakes get warmer - Trochine, Carolina (2011)
1. Filamentous green algae (FGA) may represent an alternative state in high-nutrientshallow temperate lakes. Furthermore, a clear water state is sometimes associated with thedominance of FGA; however, the mechanisms involved remain uncertain.2. We hypothesised that FGA may promote a clear water state by directly suppressingphytoplankton growth, mostly via the release of allelochemicals, and that this interactionmay be affected by temperature.3. We examined the relationships between FGA, phytoplanktonic chlorophyll a concentrationsand zooplankton in a series of mesocosms (2.8 m3) mimicking enriched shallowponds now and in a future warmer climate (0 and c. 5 C above ambient temperatures).We then tested the potential allelopathic effects of FGA (Cladophora sp. and Spirogyra sp.)on phytoplankton using several short-term microcosms and laboratory experiments.4. Mesocosms with FGA evidenced lower phytoplanktonic chlorophyll a concentrationsthan those without. Zooplankton and zooplankton : phytoplankton biomass ratios did notdiffer between mesocosms with and without FGA, suggesting that grazing was notresponsible for the negative effects on phytoplanktonic biomass (chlorophyll a).5. Our field microcosm experiments demonstrated that FGA strongly suppressed thegrowth of natural phytoplankton at non-limiting nutrient conditions and regardless ofphytoplankton initial concentrations or micronutrients addition. Furthermore, we foundthat the negative effect of FGA on phytoplankton growth increased up to 49% under highincubation temperatures. The experiment performed using FGA filtrates confirmed thatthe inhibitory effect of FGA on phytoplankton may be attributed to allelochemicals.6. Our results suggest that FGA control of phytoplankton growth may be an importantmechanism for stabilising clear water in shallow temperate lakes dominated by FGA andthat FGA may play a larger role when lakes get warmer.